2021
DOI: 10.3390/plants10030561
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Drought Stress Effects on Traditional and Modern Apple Cultivars

Abstract: Genotype-dependent responses of apples to drought stress were evaluated between commercial and traditional apple cultivars. The results indicate different mechanisms of tolerance to investigated drought stress conditions. Chlorophyll fluorescence induction (OJIP) parameters, chlorophyll and carotenoid content, malondialdehyde (MDA), hydrogen peroxide (H2O2), proline, phenols and leaf water content (WC) were measured. The traditional cultivar “Crvenka” confirmed the best tolerance to a drought stress condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 74 publications
6
31
0
Order By: Relevance
“…A stronger decline of these parameters during the drought period in modern cultivar New Star confirmed its higher drought sensitivity compared with autochthonous cultivar. In our previous research, we also observed that autochthonous apple cultivar had better photosynthetic efficiency compared to modern apple cultivar under drought conditions (Mihaljević et al 2021).…”
Section: Discussionmentioning
confidence: 73%
“…A stronger decline of these parameters during the drought period in modern cultivar New Star confirmed its higher drought sensitivity compared with autochthonous cultivar. In our previous research, we also observed that autochthonous apple cultivar had better photosynthetic efficiency compared to modern apple cultivar under drought conditions (Mihaljević et al 2021).…”
Section: Discussionmentioning
confidence: 73%
“…Jia et al [ 38 ] also found that PSI and PSII activities declined with drought stress duration in maize. A decline in PIabs at pod filling suggests an inactivation of the PSII reaction centers (RCs) [ 18 ]. Therefore, increased PIabs in AGS429 and UVE17 under drought stress shows that these cultivars may have maintained their PSII RCs and avoided photo-inhibition of both photosystems [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the accumulation of carotenoids (CRDs) of drought-stressed transgenic tobacco ( Nicotiana tabacum ), alfalfa ( Medicago sativa ) and sweet potato ( Ipomoea batatas ) plants improved membrane stability and enhanced antioxidant activity [ 15 , 16 , 17 ]. Reduction of the photosynthetic efficiency in drought-stressed apple ( Malus pumila ) trees was associated with low Fv/Fm (which represents quantum efficiency of photosystem II), performance index absorbance (PIabs) and total performance index (PItotal) [ 18 ]. In barley cultivars, Fv/Fm only decreased under severe drought stress, but PIabs was not affected [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These types of treatments also enhance the antioxidant capacity of the shoot extracts and may be the primary function of these cold-inducible flavonoids. Furthermore, investigation conducted by Mihaljevic et al [10] showed that traditional apple cultivar are more resistant to drought when compared with commercial one.…”
Section: Introductionmentioning
confidence: 99%